2019
DOI: 10.1038/s41598-019-55036-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-interval wildfire and drought overwhelm boreal forest resilience

Abstract: The size and frequency of large wildfires in western North America have increased in recent years, a trend climate change is likely to exacerbate. Due to fuel limitations, recently burned forests resist burning for upwards of 30 years; however, extreme fire-conducive weather enables reburning at shorter fire-free intervals than expected. This research quantifies the outcomes of short-interval reburns in upland and wetland environments of northwestern Canadian boreal forests and identifies an interactive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 66 publications
(109 reference statements)
7
149
1
Order By: Relevance
“…A fire resilience index could also be developed for systems where crown‐killing fire is the common fire regime, but would need to incorporate the variation in regeneration methods and optimal fire return intervals (Enright et al, 2015). In general, fire‐embracing species possessing either serotiny or resprouting ability are resilient to stand‐replacing, high‐severity fire, although with ongoing anthropogenic and climate‐driven shortening of fire return intervals in such crown‐fire‐adapted ecosystems, these species are also at risk of population declines (Enright et al, 2015; Turner, Braziunas, Hansen, & Harvey, 2019; Whitman, Parisien, Thompson, & Flannigan, 2019). Furthermore, fire‐avoiding species (Keeley, 2012) may also be resilient to stand‐replacing fire if tree establishment proceeds during sufficiently long fire‐free intervals and if post‐fire spatial mosaics of live tree refugia are complex enough for seed dispersal to initiate forest succession.…”
Section: Discussionmentioning
confidence: 99%
“…A fire resilience index could also be developed for systems where crown‐killing fire is the common fire regime, but would need to incorporate the variation in regeneration methods and optimal fire return intervals (Enright et al, 2015). In general, fire‐embracing species possessing either serotiny or resprouting ability are resilient to stand‐replacing, high‐severity fire, although with ongoing anthropogenic and climate‐driven shortening of fire return intervals in such crown‐fire‐adapted ecosystems, these species are also at risk of population declines (Enright et al, 2015; Turner, Braziunas, Hansen, & Harvey, 2019; Whitman, Parisien, Thompson, & Flannigan, 2019). Furthermore, fire‐avoiding species (Keeley, 2012) may also be resilient to stand‐replacing fire if tree establishment proceeds during sufficiently long fire‐free intervals and if post‐fire spatial mosaics of live tree refugia are complex enough for seed dispersal to initiate forest succession.…”
Section: Discussionmentioning
confidence: 99%
“…However, when reburning occurs before tree maturation, postfire seed sources are absent (Keeley et al 1999 , Brown and Johnstone 2012 , Turner et al 2019 ). In these cases, infrequent-fire forest types are vulnerable to transitions from one forest type to another (e.g., from pine to aspen; Hart et al 2019 , Whitman et al 2019 ), or to conversion from forest to grassland or shrubland (Brown and Johnstone 2012 ).…”
Section: Mechanisms Of Forest Conversionmentioning
confidence: 99%
“…Herein we found that canopy cover was the most important predictor (Figure 3), exhibiting a strong negative correlation with burn probability ( Figure 4B), so areas with high canopy cover had a lower probability to burn. Considering that taller forest stands exhibited a higher burn probability ( Figure 7), burn probability could correspond with forest succession (Whitman et al 2019). Thus, as forest stands progress from stand initiation to stem exclusion and the understory re-initiation stage (Oliver et al 1996), stand height generally increases while competition among dominant trees might lead to increased canopy openness.…”
Section: Biotic and Abiotic Influence On Burn Probabilitymentioning
confidence: 99%
“…Recent estimates suggest that over a 30-year period, the mean annual area burned in Canada's forested ecosystems for the period 1985-2015 was greater than 1.6 Mha, but varied markedly with large fire years often dominating the long-term trend (r ¼ 1.1 Mha; Coops et al 2018). Under a changing climate, a number of wildfire characteristics such as area burned, size, occurrence, and seasonality are expected to change as weather becomes more fire conducive (Boulanger et al 2014;Xi et al 2019;Whitman et al 2019), although the increase in area burned is expected to be gradual (Price et al 2013). Already, there is some evidence of recent shifts in area burned consistent with these warmer climate patterns (Kasischke et al 2010).…”
Section: Introductionmentioning
confidence: 99%